Changes in cancer incidence and stage during the COVID-19 pandemic in 2020–2021 in the Nordic countries - Anna Johansson; Anna Skog; Tom Børge Johannesen; Tor Åge Myklebust; Simon M. Kønig; Charlotte Wessel Skovlund; Lina Steinrud Mørch; Søren Friis; Marnar Fríðheim Kristiansen; David Pettersson; Eva María Gudmundsdóttir; Nanna Margrét Kristinsdóttir; et al. (Acta Oncologica)
Background and purpose: The COVID-19 pandemic impacted substantially on cancer healthcare, including the temporary suspension of screening activities. We compared cancer incidence rates and stage during 2020–2021 to pre-pandemic rates in the Nordic countries.